Un enfoque constructivista para el desarrollo del currículo en ciencias - Driver, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The differences between children's ideas and scientific thinking gives us some indication of the types of changes and the magnitude of those changes which we may be attempting to promote in young people's understanding during school years. In this paper 1 will review how such changes might be promoted and consider implications for curriculum planning.